A Genuine Trivalent Bis-Acylphosphide (BAP) Complex of Uranium - Hochholzer, Jakob; Waldschmidt, Pablo; Heinemann, Frank Wilhelm; Grützmacher, Hansjörg; Meyer, Karsten (European Journal of Inorganic Chemistry, 2024)
The genuine trivalent uranium complex, K[UIII(mesBAP)4], employing four bidentate bis(2,4,6-trimethylbenzoyl)phosphide (mesBAP) chelating ligands, is reported and obtained by the reduction of the literature-known tetravalent analog [UIV(mesBAP)4]. Hence, the bis(acyl)phosphide mesBAP ligand allowed to establish a fully reversible redox couple with uranium in the oxidation states +III and +IV. In both complexes [U(mesBAP)4]0/−, the uranium ions are coordinated to four mesBAP ligands in a square antiprismatic geometry. All new compounds have been characterized by single-crystal XRD analysis, 1H and 31P NMR, and UV/Vis/NIR electronic absorption spectroscopy, as well as SQUID magnetization and electrochemical measurements, and CW X-band EPR in the case of the trivalent complex.
CRIS-Team Scopus Importer:2024-04-26
Keywords: Bisacylphosphide BAP; Ligands; Magnetism; Spectroscopy; Uranium Complexes

CO2 Activation with Formation of Uranium Carbonate Complexes in a Closed Synthetic Cycle - Waldschmidt, Pablo; Hörger, Christopher; Riedhammer, Judith; Heinemann, Frank Wilhelm; Hauser, Christina; Meyer, Karsten (Organometallics, 2020)
A closed synthetic cycle for the transformation of carbon dioxide to carbonate with a mid-valent tris(aryloxide)-ligated uranium(IV) terminal oxo complex is presented herein. Starting from the previously reported uranium(III) complex, [UIII(OArAd,Ad,Me)3], the uranium(V) terminal oxo complex, obtained by oxidation with N2O or NO, can be reduced with KC8 to yield CO2 activating anionic uranium(IV) oxo complexes [(Ad,Ad,MeArO)3UIV(O)]-. The cycle proceeds with the formation of [(Ad,Ad,MeArO)2(κ2-Ad,Ad,MeArOCO2)UIV(μ-κ1:κ2-CO3)]- upon reaction of the oxo anion with excess CO2 that adds to the terminal oxido ligand and inserts into the uranium-aryloxide bond. Treating this complex with trimethylsilyl halide eliminates both carbonates and generates, for instance, [K(2.2.2-crypt)][(Ad,Ad,MeArO)3UIV(I)2], which can ultimately be reduced with KC8 to recover the trivalent starting material, thus closing the cycle. In contrast, reaction of the 18-crown-6 stabilized U(IV) oxo analogue with CO2 yields a rare and isolable example of a uranium complex with a μ-κ1:κ2-CO3-bound carbonate weakly interacting with the [K(18-crown-6)(THF)]+ moiety; here, CO2 insertion and formation of an aryl carbonate ligand are not observed.
CRIS-Team Scopus Importer:2020-02-04

Evaluation of Manganese Cubanoid Clusters for Water Oxidation Catalysis: From Well-Defined Molecular Coordination Complexes to Catalytically Active Amorphous Films - Hosseinmardi, Soosan; Scheurer, Andreas; Heinemann, Frank Wilhelm; Kuepper, Karsten; Senft, Laura; Waldschmidt, Pablo; Ivanovic-Burmazovic, Ivana; Meyer, Karsten (Chemsuschem, 2021)
With a view to developing multimetallic molecular catalysts that mimic the oxygen-evolving catalyst (OEC) in Nature's photosystem II, the synthesis of various dicubanoid manganese clusters is described and their catalytic activity investigated for water oxidation in basic, aqueous solution. Pyridinemethanol-based ligands are known to support polynuclear and cubanoid structures in manganese coordination chemistry. The chelators 2,6-pyridinedimethanol (H2L1) and 6-methyl-2-pyridinemethanol (HL2) were chosen to yield polynuclear manganese complexes; namely, the tetranuclear defective dicubanes [MnII2MnIII2(HL1)4(OAc)4(OMe)2] and [MnII2MnIII2(HL1)6(OAc)2] (OAc)2⋅2 H2O, as well as the octanuclear-dicubanoid [MnII6MnIII2(L2)4(O)2(OAc)10(HOMe/OH2)2]⋅3MeOH⋅MeCN. In freshly prepared solutions, polynuclear species were detected by electrospray ionization mass spectrometry, whereas X-band electron paramagnetic resonance studies in dilute, liquid solution suggested the presence of divalent mononuclear Mn species with g values of 2. However, the magnetochemical investigation of the complexes’ solutions by the Evans technique confirmed a haphazard combination of manganese coordination complexes, from mononuclear to polynuclear species. Subsequently, the newly synthesized and characterized manganese molecular complexes were employed as precursors to prepare electrode-deposited films in a buffer-free solution to evaluate and compare their stability and catalytic activity for water oxidation electrocatalysis.
CRIS-Team Scopus Importer:2021-10-08
Keywords: cubanes; electrocatalysis; electrodeposition; manganese; water splitting

Homoleptic Acetylacetonate (acac) and ?-Ketoiminate (acnac) Complexes of Uranium - Waldschmidt, Pablo; Riedhammer, Judith; Hartline, Douglas; Heinemann, Frank Wilhelm; Meyer, Karsten (Inorganic Chemistry, 2023)
Transmetalation of potassium salts of differently substituted acetylacetonate (acac) and beta-ketoiminate (acnac) with [U(I)3(dioxane)1.5] and [U(I)4(dioxane)2] resulted in the formation of homoleptic, octahedral complexes [U(tBuacnacPh)3] (with tBuacnacPh = 2,2,6,6-tetramethyl-5-(phenylimino)heptan-3-onate) in the oxidation states +III and +IV and the homoleptic, square prismatic complexes [UIV(MeacnacPh)4] (with MeacnacPh = 4(phenylimino)pentan-2-onate) and the homoleptic, square anti prismatic complexes [U(tBuacac)4] [with acac = 2,2,6,6-tetramethyl3,5-heptanedionate (tBuacac), 2,2,6,6-tetramethyl,4-methyl-3,5-heptanedionate (tBuacMeac), and 2,2,6,6-tetramethyl-4-phenyl-3,5-heptanedionate (tBuacPhac)] in oxidation states +III, +IV, and +V. Oxidation of [UIII(tBuacnacPh)3] (1) with AgOTf yielded [UIV(tBuacnacPh)3][OTf] (2), which was fully characterized by single-crystal X-ray diffraction analysis, a combination of ultraviolet/visible/near-infrared, nuclear magnetic resonance, and infrared spectroscopies, and solid-state superconducting quantum interference device magnetization studies. Complexation of the sterically less encumbering ligand derivative MeacnacPh provided access to the tetravalent, square antiprismatic complex [UIV(MeacnacPh)4] (3). Cyclovoltammetric analysis of the square antiprismatic [UIV(tBuacac)4] (4), [UIV(tBuacMeac)4] (5), and [UIV(tBuacPhac)4] (6) revealed reversible anodic and cathodic waves, attributable to the U(III/IV) and U(IV/V) redox couples, both being chemically accessible, as tested in the case of 5. The corresponding U(III) and U(V) compounds, [K(2.2.2-cryptand)][UIII(tBuacMeac)4] (7) and [UV(tBuacMeac)4][SbF6] (8), were synthesized accordingly. Unfortunately, reduced 7 proved to be too reactive for isolation and could only be detected by electron paramagnetic resonance spectroscopy. Notably, electrochemical studies on homoleptic uranium(IV) complexes with differently derivatized (R) acRac ligands (R = H, Me, or Ph) feature large electrochemical windows of up to 2.91 V, measured between the uranium(III) and the uranium(V) species, in addition to high stability toward repeated potential scans.
CRIS-Team WoS Importer:2023-03-03